Implementasi Metode Morfologi Dalam Perancangan Desain Kemasan Produk UMKM Kue Mami - Youngky Odies S; Moch Haifan F; M Farit Rusdiawan; Adam Hadiansyah; Ribangun Bamban Jakaria (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Packaging can have a significant impact on various aspects of a business, including economics, marketing, and product design. Economically, packaging can play an important role in increasing product value and marketing effectiveness to increase sales and profits. In marketing, packaging can form a brand identity with a unique and attractive packaging design, which can increase the attractiveness of a product so that it looks more professional and trustworthy. In product design, packaging can protect the product from damage and provide safe storage for the product.